Collusive effects of a monopolist's use of an intermediary to deliver to retailers - Isabel Teichmann; Vanessa von Schlippenbach (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
A manufacturer contracting secretly with several downstream competitors faces an opportunism problem, preventing it from exerting its market power. In an infinitely repeated game, the opportunism problem can be relaxed. We show that the upstream firm's market power can be restored even further if the upstream firm chooses a mixed distribution system in which it makes use of an intermediary to distribute the good to a subset of the retailers and delivers directly only to the remaining downstream firms.
Keywords: L12; L14; L42; 330; Vertical relations; Delegation; Downstream Monopolization; Commitment problem; Channel structure; Multi-tier industry